HiperLAN/2: OFDM simulation using Simulink / Nor Azrina Mohammad Yusuf - Mohammad Yusuf, Nor Azrina (2004)
Orthogonal Frequency Division Multiplexing (OFDM) is a new digital modulation technique, which consists of transmitting a data stream on several carries instead of using single carrier. It is adopted in several recent digital wireless broadcast and network standards, including HiperLAN/2, IHEE802.11a and Digital Audio Broadcasting (DAB) This project paper will explore of the use of Simulink to model features of OFDM receiver design. This thesis will also discuss the implementation of OFDM in HiperLAN/2 by simulation using Simulink to model features of OFDM receiver designs, in packet based and in continuous transmission systems, including synchronization and channel compensation problems.